2012
DOI: 10.1111/j.1360-0443.2012.03889.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of major depressive disorder and gender to changes in smoking for current and former smokers: longitudinal evaluation in the US population

Abstract: Aims Although depression and smoking are highly correlated, the relationship of Major Depressive Disorder (MDD) to smoking cessation and relapse remains unclear. This study compared changes in smoking for current and former smokers with and without Current and Lifetime MDD over a three year period. Design Analysis of two waves of longitudinal data from the National Institute on Alcohol Abuse and Alcoholism’s National Epidemiologic Survey on Alcohol and Related Conditions (Wave 1, 2001–2002; Wave 2, 2004–2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 50 publications
(69 reference statements)
7
55
2
1
Order By: Relevance
“…Spending up to 25% of their income on cigarettes (5) and consuming 44% of purchased cigarettes in the United States (6), adults with BHCs are affected disproportionately by tobacco-related diseases and die, on average, 25 years prematurely (7)(8)(9)(10)(11). Although overall smoking prevalence (12) and severity of nicotine dependence among smokers have declined in recent decades (13,14), the decreases have been smaller or nonexistent among persons with BHCs (14)(15)(16)(17)(18). This suggests that smoking-related disparities between persons with and without BHCs may be increasing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spending up to 25% of their income on cigarettes (5) and consuming 44% of purchased cigarettes in the United States (6), adults with BHCs are affected disproportionately by tobacco-related diseases and die, on average, 25 years prematurely (7)(8)(9)(10)(11). Although overall smoking prevalence (12) and severity of nicotine dependence among smokers have declined in recent decades (13,14), the decreases have been smaller or nonexistent among persons with BHCs (14)(15)(16)(17)(18). This suggests that smoking-related disparities between persons with and without BHCs may be increasing.…”
mentioning
confidence: 99%
“…However, advice to quit and resources for quitting may be less accessible for those with BHCs, in part because of inequitable access to high-quality health care. Existing research on longitudinal disparities in smoking among adults with and without BHCs has primarily used data from national surveys (14)(15)(16)(17)(18). It is unknown whether smoking disparities also persist within an integrated health care delivery system with convenient and affordable access to smoking cessation interventions.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] Women more frequently report that smoking helps them control stress and negative mood and manage their weight, and are more likely to relapse to smoking after a quit attempt. [27][28][29][30][31] Accordingly, a meta-analysis of smoking cessation studies reported that women in general require more intensive counseling support for quitting than their male counterparts. 25 As a relative comparison, Korean women smokers valued the support that they received from their therapists more than their male counterparts.…”
Section: Kim Et Almentioning
confidence: 99%
“…Both smoking and depression are major public health problems with high morbidity and mortality [1][2][3][4]. Individuals with depression are almost twice as likely to be smokers [5][6][7], have lower long-term smoking abstinence (OR=0.81, 95% CI=0.67-0.97) [1], and experience greater addiction severity and negative mood when quitting smoking [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%